The influence of the competitive landscape on cross-functional interactions between procurement and engineering. Issue 1 (January 2020) - Ashenbaum, Bryan; Blair, Cynthia Wallin; Brewer, Barry
Abstract: This study assesses the extent to which a firm's external environment shapes the cross-functional interactions between procurement and engineering, utilizing an embedded multiple-case study methodology. In summary, we found that high environmental ambiguity discourages procurement-engineering mutual understanding. High environmental uncertainty with moderate ambiguity, on the other hand, appears to foster both mutual understanding and inter-functional collaboration. Overall, procurement personnel are more optimistic than engineering personnel regarding the performance results stemming from cross-functional integration. Additionally, increasing job tenure for procurement personnel leads to a higher level of perceived integration with engineering, while engineers with longer job tenure report see less value in collaborating with procurement, often creating an asymmetric power distribution with engineering taking a dominating role. Highlights: High ambiguity discourages procurement-engineering mutual understanding. High uncertainty/moderate ambiguity fosters mutual understanding and collaboration. Purchasers report higher performance benefits from collaboration than engineers. Longer-tenured purchasers perceive higher value collaborating with engineering. Longer-tenured engineers perceived lower value collaborating with procurement.